Antidiabetic Effect of Artemether in Db/Db Mice Involves Regulation of AMPK and PI3K/Akt Pathways - Bai, Xiaolin; Pei, Ruixia; Lei, Wen; Zhao, Meiyun; Zhang, Jialin; Tian, Lu; Shang, Junke (Frontiers in Endocrinology, 2020)
The traditional Chinese medicine has long been used in the treatment of diabetes, one major disease threatening the public health. It has been reported that artemether exerts antidiabetic effects on type 2 diabetes in db/db mice, however the underlying mechanisms remain unknown. In the present study, we show that artemether regulates expression of related enzymes participating in the glucose and lipid metabolism in the liver of db/db mice, which could at least partly explain the improved glucose and lipid metabolism in artemether-treated mice. Additionally, artemether also regulates expression of glycogen synthesis related enzymes in the skeletal muscle of db/db mice, supporting its promotive role in glycogen synthesis. Mechanistically, artemether activates AMPK pathway as well as PI3K/Akt pathway in the liver and skeletal muscle of db/db mice, suggesting that these two signaling pathways are both involved in the antidiabetic effects of artemether on type 2 diabetes in db/db mice. In conclusion, our study connects the antidiabetic effects of artemether to the regulation of metabolic enzymes and signaling pathways, and also provides molecular basis for the potential application of artemether in treating type 2 diabetes.